Let $F(x)$ be an arbitrary continuously differentiable function, and consider the following differential equation

$$ y'+ \frac{F'(x)}{F(x)}y= \frac{1}{F(x)}.$$

If I use the Integrating Factor which says that for an equation $$ y'+ P(x)y= Q(x),$$

the general solution is

$$ y=e^{-\int P(x)dx}\int Q(x)e^{\int P(x)dx}dx+Ce^{-\int P(x)dx}.$$

Using the fact that

$$\int \frac{F'(x)}{F(x)} dx = \ln(F(x)), $$

this simplifies to

$$ y=(1+C)F(x)^{-1}.$$

However, if I substitute this solution into the initial differential equation I get

$$ -\frac{(1+C)F'(x)}{F(x)^2} + \frac{F'(x)}{F(x)}\frac{(1+C)}{F(x)} = \frac{1}{F(x)}, $$


$$ 0 = \frac{1}{F(x)}. $$

Where is my mistake?

  • $\begingroup$ $\int 1 \neq 1$ $\endgroup$ Apr 3, 2020 at 20:18
  • $\begingroup$ Rewrite the differential equation as $(y'F+F'y)=1$ and note that the LHS is $(yF)'$. $\endgroup$
    – dan_fulea
    Apr 3, 2020 at 20:25
  • $\begingroup$ Your solution for y is not correct. That's why when you plug it in the DE it gives you something wrong. $\endgroup$ Apr 3, 2020 at 20:37

1 Answer 1


You don't really need an integrating factor: $$y'+ \frac{F'(x)}{F(x)}y= \frac{1}{F(x)}$$ $$F(x)y'+ F'(x)y= 1 $$ $$(F(x)y)'= 1$$ $$F(x)y= x+c$$ $$ \implies y(x)= \dfrac {\color{blue}{x+c}}{F(x)}$$ And not $y(x)= \dfrac {\color{red}{1+c}}{F(x)}$

$$y=e^{-\int P(x)dx}\int Q(x)e^{\int P(x)dx}dx+Ce^{-\int P(x)dx}.$$ $$y=\dfrac {1}{F(x)}\int dx+\dfrac C{F(x)}$$ $$y=\dfrac {x}{F(x)}+\dfrac C{F(x)}$$

  • 1
    $\begingroup$ In the first step, you are using $F$ as integrating factor, you multiply the equation with it to get integrable expressions. You are just not using the formula for it. $\endgroup$ Apr 4, 2020 at 5:20
  • $\begingroup$ Yes that's true @LutzLehmann I just multiplied the equation by $F(x)$ Then I integrated the DE. $\endgroup$ Apr 4, 2020 at 5:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.